(untitled) - Ishikawa, Shigeru (Tokyo, Japan, 1981)
These assays have attempted to study some of the most urgent and most basic issues of contemporary economic development.
Keywords: Agriculture and state,Green Revolution,Nhà nước và nông nghiệp,Cách mạng xanh; Social aspects,Khía cạnh xã hội; Asia,Asia,Châu Á,Châu Á